Persepsi Mahasiswa terhadap Penggunaan Moodle dalam Pembelajaran Bahasa Jerman: Analisis Antarangkatan Berbasis Technology Acceptance Model - Daarussyifa, Arfina; Permatawati, Irma; Permana, Pepen (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
Previous studies on Moodle use in higher education have generally treated students as a homogeneous group, thereby overlooking potential variations in perceptions across cohorts with different learning experiences. This study addresses this gap by examining cohort-based differences in student perceptions of Moodle use in German language learning through the framework of the Technology Acceptance Model (TAM). Specifically, this study investigates differences in perceptions among students of the German Language Education Study Program at FPBS UPI based on four TAM constructs: perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention. Data were collected through a questionnaire involving 246 students from four cohorts and analyzed using descriptive and comparative statistical approaches. The results indicate statistically significant differences at the global level in perceived usefulness and behavioral intention; however, the effect sizes were small, suggesting that the variations were limited in practical terms. Further analysis reveals that differences in perceived usefulness primarily involve the 2019 cohort in comparison with the 2020 and 2021 cohorts, while no significant differences were found across cohort pairs for the other constructs. These findings suggest that variations in student perceptions across cohorts are more closely related to evaluations of system usefulness rather than ease of use or attitudes toward Moodle. Therefore, Moodle development should focus on pedagogical integration that is adaptive to differences in cohort experiences, such as providing usage support for early cohorts and optimizing interactive learning activities for more experienced cohorts.